Role of Systemic Treatment for Advanced/Metastatic Gastric Carcinoma in the Third-Line Setting: A Bayesian Network Analysis - Pan, Wen-Tao; Zhou, Su-Na; Pan, Meng-Xian; Luo, Qiu-Yun; Zhang, Lin; Yang, Da-Jun; Qiu, Miaozhen (Frontiers in Oncology, 2020)
Background: Increasing evidences from phase II or III trials have proved that salvage systematic therapy, including chemotherapy, target therapy or immune checkpoint inhibitor can prolong survival in patients who are failure to second line therapy, yet there are no guidelines for the optimum third-line treatments. To compare the effectiveness and safety of currently third-line therapies for metastatic Gastric Cancer (mGC), we conducted this network analysis. Methods: The literatures up to Sep 30, 2019 were systematically searched and analyzed by a Bayesian fixed-effect model. Results: This study included seven randomized clinical trails which involved 2655 patients. It turns out that for overall survival, nivolumab has the highest probability to be the optimal choice for overall survival (OS). For patients with no peritoneal metastases, the network meta-analysis showed that Nivolumab (HR:0.64; 95% CI: 0.48–0.85) and Trifluridine/tipiacil (HR:0.66; 95% CI: 0.51–0.86) were associated with significantly higher improvement in OS than placebo. However patients with peritoneal metastases could not get benefit from nivolumab, ramucirumab or Trifluridine/tipiacil, when compared with placebo. For progression-free survival, apatinib(850mg) was the most likely candidate,followed by ramucirumab. Statistically, Apatinib(850mg), Trifluridine/tipiacil and SLC had higher incidences of high-grade adverse events (AEs) than placebo. Conclusion: Our findings demonstrate that nivolumab has the best balance between acceptability and effictiveness in the third line therapy for mGC.